Jeff: the hungry fish; a case study in educational game design with unity 3D and C - Rasmaliza Rashid; Muhammad Aqil Shah Mohamad; Sharifah Nurulhuda Tuan Mohd Yasin (Journal of Educational and Learning Studies, 2025)
‘Marine Fantasy’ comes in the form of a game entitled “Jeff: The Hungry Fish”, created to encourage people in understanding marine biology - the fun way!. The gaming experience named ‘Jeff: The Hungry Fish’ presents a concept known as ‘Marine Fantasy’ with the intention of promoting comprehension of marine biology among individuals, albeit in an entertaining way. Concurrently, developing this new project meant being outside our comfort zone. That will lead to a break-through of stunning visuals, fresh musical pieces and far more efficient coding scripts. Along with this report, it proposes a simple yet educational game, developed in Unity 3D, scripted in C# language. The game immerses the player in the role of Jeff, a fish aspiring to progress into a larger and more powerful aquatic creature. Given its low position in the food chain, participants are required to adhere to the regulations of underwater existence while engaging in the gameplay. "Jeff: The Hungry Fish" is an educational game, but not in the traditional sense of a structured academic curriculum. Instead, it embraces a broader definition of education, one that encompasses learning through diverse modalities and across various domains. The game utilizes a playful and engaging approach to impart knowledge and information, recognizing that learning can occur through experiences that are both entertaining and enriching. The educational aspect of "Jeff: The Hungry Fish" lies in its potential to foster curiosity, promote critical thinking, and provide opportunities for exploration and discovery. It aims to make learning a more enjoyable and accessible experience, regardless of the specific subject matter or the learner's background.